PDTM-15. IDENTIFICATION AND CHARACTERIZATION OF WILMS' TUMOR PROTEIN IN PEDIATRIC MIDLINE GLIOMAS. (5th November 2018) - Lee, Sulgi; Kambhampati, Madhuri; Yadavilli, Sridevi; Gordish-Dressman, Heather; Santi, Mariarita; Cruz, Conrad; Packer, Roger; Almira-Suaurez, Isabel; Hwang, Eugene; Nazarian, Javad
Abstract: Pediatric midline gliomas, especially those associated with the pons, known as diffuse intrinsic pontine gliomas (DIPGs) are deadly pediatric brain cancer that makes up 10–15% of all central nervous system (CNS) tumors in children. Its anatomical location and infiltrative nature makes it one of the most challenging tumors to treat. Targeted therapies are gaining more interest in CNS tumors. Identification of tumor associated antigens is one of many requirements in developing an effective targeted therapy. Wilms' tumor protein (WT1) has been ranked number 1 cancer immunotherapy target by National Cancer Institute. Many types of solid tumors have been shown to express WT1 and it is being examined as one of potential immunotherapeutic targets. Here we validated WT1 as a potential tumor associated antigen in pediatric diffuse midline gliomas using formalin fixed paraffin embedded (FFPE) tumor and adjacent healthy specimens, fresh frozen post-mortem tissues and patient-derived DIPG primary cell lines. Our immunohistochemistry (IHC) staining of patient FFPE specimens showed strong WT1 immunoreactivity in tumor compared to adjacent normal tissue. Western blot of tumor tissues and cell lines were performed to further validate WT1 levels in the tumors versus adjacent healthy tissues. Interestingly, tumors showed cytoplasmic expression of WT1. In addition, H3.1K27M subtype gliomas showed weak to absent WT1 immunoreactivity compared to strong to moderate in H3.3K27M subtypes. Western blots also validated the differential expression of the protein. Our study suggests that WT1 is a potential tumor specific antigen in pediatric midline gliomas, which can be utilized for targeted therapies such as immunotherapy.